Penentuan Kondisi Optimum Ekstraksi Ion Timbal(II) Menggunakan Teknik Emulsi Membran Cair - Alam, Syamsu; Hamzah, Baharuddin; Nuryanti, Siti; Nurbaya, Siti (Jurnal Akademika Kimia, 2014)
A research on the extraction of lead(II) ion has been done using emulsion liquid membrane technique. This research used a laboratory experiment method by using benzoyl acetone as a carrier, paraffin liquid as the membrane, a solution of nitric acid as an internal phase, Span-80 as surfactant, and a solution of lead(II) as the sample solution. This research was conducted to determine the optimum extraction condition of lead(II) ions in solution which includes a volume ratio of emulsion to external phase and extraction capacity of lead(II) ion by emulsion liquid membrane technique. The volume ratio of emulsion to external phase used was 1:5, 1:6, 1:7, and 1:8. While the variation of concentration of lead(II) used was 220 ppm, 434 ppm, 695 ppm, and 817 ppm. The determination of the concentration of lead(II) ions in external phase is done by using a spectrophotometer SpectroDirect. The results of this research showed that the volume ratio of emulsion to external phase were in the maximum extraction percentage; 1:6 ratio. Moreover, the concentration of lead(II) were in maximum extraction percentage of 220 ppm with extraction percentage of 56.36%.